O Idoso e a apropriação das tecnologias de informação e comunicação no universo digital - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This research aims to identify and analyze the appropriation of the elderly use of Information and Communication Technologies and verify that it causes changes in your daily life or it interferes. Specifically, we intend to identify what motivates seniors to attend workshops Informatics and which technology is preferred by them. It also intends to demonstrate the contributions that the workshops on Information and Communication Technologies (ICT) offered at the Centro de Convivência (CC), have given to the elderly are able to take ownership of technological resources to solve their everyday problems. We opted for a qualitative study, based on conceptions of Lüdke and Andrew (2013) and Chizzotti (2005). It used a theoretical framework that allows us to understand the conceptual dimension of the problem studied. Regarding the elderly have Beauvoir (1990), Cachioni (2004), Kertzman (2004), Oliveira (2008), Mercadante (1998), Guimaraes; Ramos (2012). Regarding Information and Communication Technologies used: Frias (2011), Martinez (2006), Santaella (1992), Castells (2005) and to understand the everyday use the reference Heller (2008). Data collection was carried out during the workshops in DC, organized to target public service. The instruments used for data collection were half-open questionnaires to course participants, targeted and monitored way. We can see that the process of learning and the discovery of how to use ICT brought greater motivation to the elderly and aspiration for better interaction with the family and in their daily lives, and to encourage the appropriation of technologies offered in the workshops.
Keywords: Idosos e Tecnologias da Informação e Comunicação; Formação de Idosos com as TIC; Elderly and information and comunication Technologies; Senior training with ICT; CIENCIAS HUMANAS::EDUCACAO